Effect of Spacing and Cobalt Application Methods on Root Nodulation and Yield of kabuli Chickpea (Cicer kabulium L.) Cultivars - Terin, Prakash; Gudadhe, N. N.; Madagoudra, Y. B.; R., Lokesh; Terin, Basavaraj (International Journal of Economic Plants, 2022)
A field experiment was conducted at the College Farm, N. M. College of Agriculture, Navsari Agricultural University, Navsari to study the effect of spacing and cobalt application on kabuli chickpea (Cicer kabulium L.) cultivars. The treatments of the study included eighteen treatment combinations consisting of three varieties. Two spacing and three-cobalt application methods were evaluated by using factorial randomized block design (FRBD) with three replications. Significantly highest nodule number plant-1 (56.02), nodule fresh (2.61 g) and dry weight (0.25 g), seed yield (1497.07 kg ha-1), stover yield (2243.87 kg ha-1) were achieved with variety PKV2 (V3) followed by variety Kripa. The variety Kripa (V2) recorded numerically higher harvest index (40.39). The crop sown at spacing 60×10 cm2 (S2) produced maximum number of nodules plant-1 (53.64), nodule fresh (2.50 g) and dry weight (0.23 g) but only dry weight of root nodules was found at par with 45×10 cm2 spacing (S1) (0.21g). Significantly higher seed and stover yield (1274.51 and 2191.95 kg ha-1) and Harvest index (42.16%) were obtained with spacing 45×10 cm2 (S1). In case of cobalt application methods, significantly highest number of root nodules plant-1 (54.31), maximum fresh (2.54 g) and dry weight (0.25 g) of nodules, seed and stover yield (1520.51 and 2249.40 kg ha-1) were obtained under application of cobalt as foliar spray at 0.01%.